Metastatic brain disease in early stage ovarian cancer: A case report - Sophia Halassy; Katrina Au; Nishan Chobanian (Elsevier, 2020)
Ovarian cancer rarely metastasizes to the brain. If it does, it is more likely to occur with advanced stage carcinomas, more than one year after diagnosis, and rarely presents as a single lesion. Early detection, treatment, and close follow-up is essential to optimize prognosis and prevent long-term disability. This case presents a 54-year-old female with a previously diagnosed & treated stage 1a, grade 3 ovarian cancer who presented with a complaint of persistent headache. Imaging demonstrated a singular brain lesion. She underwent mass resection with pathology consistent with metastatic ovarian cancer. This was only 18 months after her primary diagnosis, demonstrating the importance of close surveillance and heightened awareness of metastatic disease.